Analisis Pengumuman Akuisisi Terhadap Return Saham Bank Umum di Bursa Efek Indonesia Periode 2005-2011 - M. Sienly Veronica; Anis Putri Kusuma (Conference In Business, Accounting, And Management (CBAM), 2012)
The purpose of this study was to see whether there is a difference between the stock returns before and after the acquisition as long as there are differences of opinion as to whether or not the difference between the stock returns before and after the acquisition, because of that it is interesting to do the research again. In this research, the sample used is a bank that there are only three banks acquired during the period 2005-2011. By using a period of 22 days before and 22 days after the acquisition, and Wilcoxon test method for abnormal data obtained using Î± of 0.05 then the result that there is no difference between the stock returns before and after the acquisition, it happens because of a lack of information regarding the incident acquisition so that investors receive the information at the time of acquisition or late events know.Keywords: Acquisitions, and Bank Stock Return